1940
DOI: 10.1042/bj0340580
|View full text |Cite
|
Sign up to set email alerts
|

Relation of skin lesions in the rat to deficiency in the diet of different B2-vitamins

Abstract: A NOTICEABLE feature about the earlier studies of the " dermatitis " occurring in rats when they are deprived of the heat-stable B-vitamins has been the irregularity of its incidence. The occurrence of two different types of skin lesions developing under these conditions was foreshadowed in earlier work [Chick & Roscoe, 1928, p. 795; Chick & Copping, 1930, p. 933] and has been more clearly demonstrated in recent investigations. As the members of the vitamin B2 complex have gradually been separated from one ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1940
1940
1970
1970

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In addition, the signs produced by force-feeding the deficient rats were similar to those described by Forbes & Vaughan (1954) when rats were force-fed a diet low in methionine. However, these authors found similar signs with diets low in histidine and some of these signs, particularly the appearance of porphyrins on the nose and feet, have been reported in deficiencies of nicotinic acid (Krehl, Sarma, Teply & Elvehjem, 1946) and of pantothenic acid (Chick, Macrae & Worden, 1940). Other workers have also shown that Zn deficiency produced changes in oxidation and incorporation of methionine into protein (Hsu, Anthony & Buchanan, 1969), in the incorporation of glycine into glutathione and in the pattern of plasma and liver free amino acids (J. Quarterman & E. Florence, unpublished observations).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the signs produced by force-feeding the deficient rats were similar to those described by Forbes & Vaughan (1954) when rats were force-fed a diet low in methionine. However, these authors found similar signs with diets low in histidine and some of these signs, particularly the appearance of porphyrins on the nose and feet, have been reported in deficiencies of nicotinic acid (Krehl, Sarma, Teply & Elvehjem, 1946) and of pantothenic acid (Chick, Macrae & Worden, 1940). Other workers have also shown that Zn deficiency produced changes in oxidation and incorporation of methionine into protein (Hsu, Anthony & Buchanan, 1969), in the incorporation of glycine into glutathione and in the pattern of plasma and liver free amino acids (J. Quarterman & E. Florence, unpublished observations).…”
Section: Discussionsupporting
confidence: 63%
“…This is particularly true of the deficiency syndrome which characterizes avita¬ minosis of the B2 group. A comprehensive summary of these symptoms has been published recently [Chick, Macrae & Worden, 1940]. The peculiar phenomenon of the greying of the hair of black rats deprived of a vitamin, recently shown to be distinct from the group, deserves special mention in this connexion [cf.…”
Section: Discussionmentioning
confidence: 99%
“…was equivalent to 6 g. of the original liver. It was found unsatisfactory to give a starch diet in tests for vitamin B6, as all cereal starches contain some of this vitamin [Chick, Macrae & Worden, 1940]. After some preliminary experiments it was found satisfactory to give the basal diet and supplements other than vitamin B6 for a standard period of 14 days before administering the test material.…”
Section: Methodsmentioning
confidence: 99%